(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This paper presents a comprehensive analysis of the limitations, uncertainties, and drawbacks associated with residual water return systems from fire hose lines based on vacuum methods. The key factors affecting the efficiency of water recovery are examined, including hydraulic losses, two-phase flow behavior, hose deformation, and operational conditions. Measurement uncertainties and their impact on experimental results are also evaluated. It is shown that the effectiveness of water return strongly depends on the hose length, configuration, and technical condition of the equipment. The obtained results highlight the need for improved modeling approaches and more reliable system designs.